The Role of Health Promotion Hospital in Fulfilling Patient and Family Right in RA. Basoeni Hospital, Mojokerto - Manfaati, Rizka Lina; Soedirham, Oedojo; Triyoga, Rika S; Bastian, Ardi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-